Transformational Leadership on OCB with the Mediating Role of Organizational Culture - Sabbrina, Hanifa; Sandi, Hendrik Heri (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to analyze the influence of transformational leadership on Organizational Citizenship Behavior (OCB) with the mediating role of organizational culture among employees of Hotel Daima Padang. The reason for conducting this study is the discovery of low levels of OCB through a pre-survey, as well as the importance of leadership and organizational culture in improving OCB in the hospitality industry. The method used in this study is a quantitative approach with a census technique involving 54 respondents. To analyze the data, Structural Equation Modeling-Partial Least Square (SEM-PLS) was used with the assistance of SmartPLS software. The findings of the study indicate that: (1) transformational leadership has a positive and significant influence on OCB (β = 0.658, p = 0.000), (2) transformational leadership has a positive and significant influence on organizational culture (β = 0.634, p = 0.000), (3) organizational culture positively and significantly influences OCB (β = 0.567, p = 0.000), and (4) organizational culture significantly mediates the relationship between transformational leadership and OCB (β = 0.363, p = 0.000). This study also confirms Social Exchange Theory (SET) as a theoretical foundation, which shows that the reciprocal relationship between leaders and employees results in additional work behavior. The results of this study provide practical contributions for the management of Hotel Daima Padang to strengthen the transformational leadership approach and create a collaborative work culture to support OCB in a sustainable manner.